Cancer tolerance, resistance, pathogenicity and virulence: deconstructing the disease state. (June 2016) - van Niekerk, Gustav; Loos, Benjamin; Nell, Theo; Engelbrecht, Anna-Mart
Immunologists have recently taken note of the fact that a host not only resists infection, but also exhibits a capacity to manage the pathology associated with such infection – a concept referred to as tolerance. Here we explore how the tolerance/resistance (T/R) framework can be implemented within an oncological context and explore a number of implications. In particular, the T/R framework distinguishes between pathology manifesting from extensive tumor burden, versus cancers intrinsically expressing a more pathogenic phenotype. Consequently, the T/R framework provides novel methodology in studying the nature of cancer pathology and for marker identification. Additionally, this framework may aid in redefining the therapeutic end point under suitable circumstances: establishing cancer as a chronic, manageable disease.